A Minority, Urban, and Cosmopolitan Group From an International Migration in Colonial Context: Spatialities and Identities of the Indians of Antananarivo, Madagascar - Catherine Fournet-Guérin (Migrating Minds)
The Indians of Antananarivo, a tiny minority of the urban population of Madagascar’s capital, are an original social group descending from a long-standing migration throughout the Indian Ocean in a colonial context. Although they have been living in the city for several generations and often occupy dominant social positions in terms of standard of living, they are still considered foreigners by local society and are subject to stigmatization. They form a heterogeneous group, connected to the outside world through an asserted Indian identity, as well as local and international links. Thinking in terms of cosmopolitanism allows us to consider both their urban spatial anchorage and their circulations in an open, globalized world. The presence of Indians in Antananarivo, here studied throughout leisure places and cultural venues run by Indians, contributes to the city’s cosmopolitanism, albeit rarely recognized and often devalued. On an international scale, many of them develop multiple identities, ambiguously turned towards contemporary India, and above all towards France--due to the colonial past–-and close islands, in a reticular manner. In their multiple and variable identities, the Indians of Antananarivo, though numerically very marginal, synthesize many conditions of the contemporary world: postcolonial, diasporic, minority, and cosmopolitan all at once.